The role of tourism and sightseeing in the social integration of people with disa - Lubarska, Anna (Turystyka i krajoznawstwo, 2021)
This article presents the issue of the social integration of those with disabilities in the context of tourism. It briefly discusses the action taken so far by the academic community in order to systematise and disseminate knowledge about this phenomenon. Notions of social inclusion and integration, as well as the benefits of including tourism and sightseeing in both these processes, are discussed. In this part, doubts and difficulties connected with the organisation of joint tourist trips for those with and without disabilities were presented.